2018
DOI: 10.1084/jem.20171696
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 is required for EGF-R–induced intestinal tumors via IL-6 trans-signaling

Abstract: Schmidt et al. show that loss of the membrane-bound metalloprotease ADAM17 led to impaired intestinal cancer development in the murine APCmin/+ model, which also depended on IL-6 trans-signaling via the soluble IL-6R and could be blocked by the specific IL-6 trans-signaling inhibitor sgp130Fc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 84 publications
(135 reference statements)
0
76
1
Order By: Relevance
“…Accordingly, bazedoxifene treatment also reduced the growth of patient‐derived colon cancer organoids that harbor the APC driver, and possibly compounding additional mutations. However, given that conventional IL11 signaling and IL6 trans‐signaling both facilitate the growth of intestinal tumors (Putoczki et al , ; Schmidt et al , ), our observations do not address the relative contribution by which the bazedoxifene effect is mediated through inhibition of each of these mechanisms. Given the collective contribution of these gp130 cytokines in driving tumorigenesis, bazedoxifene may represent a potent mode for the simultaneous inhibition of conventional IL11 and IL6 trans‐signaling in tumors.…”
Section: Discussionmentioning
confidence: 81%
“…Accordingly, bazedoxifene treatment also reduced the growth of patient‐derived colon cancer organoids that harbor the APC driver, and possibly compounding additional mutations. However, given that conventional IL11 signaling and IL6 trans‐signaling both facilitate the growth of intestinal tumors (Putoczki et al , ; Schmidt et al , ), our observations do not address the relative contribution by which the bazedoxifene effect is mediated through inhibition of each of these mechanisms. Given the collective contribution of these gp130 cytokines in driving tumorigenesis, bazedoxifene may represent a potent mode for the simultaneous inhibition of conventional IL11 and IL6 trans‐signaling in tumors.…”
Section: Discussionmentioning
confidence: 81%
“…Here, we found that increased activity of meprin β on the cell surface reduced cell proliferation. Another pathway influenced by ADAM17, emerging in different tumor entities, is interleukin 6 (IL-6) and IL-6R-induced trans-signaling (Bergmann et al, 2017;Schmidt et al, 2018). Here, ADAM17 releases the IL-6R from the cell surface of one cell, and then this soluble receptor forms a signaling complex together with its cytokine and gp130 (also known as IL6ST) on another cell to induce cell survival via STAT3 phosphorylation (Schaper and Rose-John, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In combination, these metagenomics markers and the standard fecal occult blood test even showed an improved sensitivity at the same level of specificity, thus improving the accuracy of diagnosis. Emerging data suggest that certain groups of bacteria might promote whereas others might protect against colon cancer ( Couturier-Maillard et al, 2013 ; Radulovic et al, 2018 ; Schmidt et al, 2018 ). Indeed, F. nucleatum seems to play a central role in the tumor microenvironment as its abundance correlates with cancer progression as well as the dysbiotic tumor microbiota composition including Bacteroides , Selenomonas , and Prevotella species.…”
Section: Microorganisms Modulate Cancer Susceptibility and Developmenmentioning
confidence: 99%